Identification and analysis of factors affecting the level of Kazakhstan's shadow economy - Tleppayev, Arsen; Khalitova, Madina; Panzabekova, Aksana; Ruzanov, Rashid; Nurymova, Saule (Asian Economic and Financial Review, 2025)
The shadow economy in Kazakhstan accounted for 17.52% of GDP in 2023 and is projected to decline to 15% by 2025, highlighting the need for a deeper understanding of its driving factors. This study aims to identify and analyze the key macroeconomic determinants influencing the size of Kazakhstan's shadow economy, focusing on income, unemployment, and gross regional product (GRP). This quantitative study utilizes secondary panel data from Kazakhstan's 16 regions from 2013–2022. A fixed-effects panel regression model was employed to estimate the impact of economic variables on the shadow economy. The regression analysis reveals that a 1% increase in monetary income leads to a 0.65%–1.16% reduction in the shadow economy. In comparison, a 1% increase in unemployment is associated with a 1.38% decrease in informal economic activities. Conversely, a 1% rise in GRP correlates with a 0.55% increase in the shadow economy, suggesting that economic expansion alone does not curb informality but may create more opportunities for unregulated activities. This research contributes to the empirical literature on transition economies, providing a regionally disaggregated analysis of the shadow economy in Kazakhstan and offering valuable insights for policymakers aiming to improve economic formalization.